The Principle of Presumption of Validity as Immunity and Legal Protection for Notaries in Making Authentic Deeds - Nafisah, Durorun; Hafidz, Jawade; Djunaedi, Djunaedi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to determine and analyze the principle of presumption of legality as immunity and legal protection for notaries in making authentic deeds. The type of research is normative legal research using the statute approach, case approach, and conceptual approach derived from secondary data sources containing primary legal materials, secondary legal materials, and tertiary legal materials. Based on the research, it is concluded that the Principle of Presumption of Validity (Presumptio Lustae Causa) means that a Notarial deed must be considered valid and binding on the parties until a party declares the deed invalid by filing a civil lawsuit with a general court. The Notarial Deed remains valid and binding on the parties or anyone interested in the deed, during and throughout the course of the lawsuit until a court decision has permanent legal force (inkrah). The parties who file a lawsuit with the court for the invalidity of the Notarial deed must be able to prove the invalidity of the Notarial deed from its external, formal, and material aspects. Preventive steps that must be adhered to and carried out by a notary in making an authentic deed so that they are free from civil sanctions and administrative sanctions are by complying with and implementing the provisions in the Notary Law.